Peran Kelompok Kerja Guru (KKG) Rumpun PAI dalam Meningkatkan Kualitas Pembelajaran Fikih - Kholil, Moh. (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
The fiqh subject teacher is the spearhead in instilling the right way of worship. However, in fiqh, teachers show various competencies and qualifications that need to be improved. For this reason, there must be a strategy for increasing professionalism in teachers through organizations in madrasas, namely the PAI clump KKG for a better desire. This research is qualitative research with a grounded theory design. Data collection techniques used participant observation, in-depth interviews, and documentation. Meanwhile, the researcher used the following steps for data analysis: data reduction, data display, and concluding. The results of the study, namely: (1) The reality of the main tasks of the PAI cluster KKG in Ngancar District have been running, including being a forum for teacher activities, compiling programs, and conducting program evaluations; (2) The efforts of the PAI cluster KKG in improving the quality of fiqh learning in MI in all districts. Ngancar is still limited to PAI lessons in general so specifically fiqh lessons have not been considered so and the quality of fiqh learning is still not as expected